Preparing athletes with intellectual disabilities for powerlifting meets - Kozub, F. M.; Reed, J. (Strength and Conditioning Journal, 2017)
Powerlifting is a popular leisure activity and an international sport for elite lifters from all backgrounds. This includes athletes with intellectual disabilities (id) who participate in segregated regional, state, national, and international special olympics powerlifting events. Furthermore, integrated formats supported by various state powerlifting organizations are also open to trained powerlifters with id. To assist coaches training lifters with unique needs, this article provides evidence-based practices from adapted physical education. The recommended training includes combining task analysis, prompting, and partial participation with a specific focus on safe and successful meet preparation for lifters with id. For a video abstract of this article, supplemental digital content 1 (see video, http://links.lww.com/scj/a219) can be referred.